Nonlocal problem for a single fourthorder equation - Abulov M. O; Tursunov B.A. (Genius Journals, 2022)
This paper examines a nonlocal problem for a single fourth-order equation. If some conditions are met, the existence and uniqueness of the solution of the problem are proved on the right side of the equation.
Keywords: Non-local task; conjugate problem; fourth-order equalization